Model Aplikasi Distribusi Santunan Korban Bencana Alam Pada Dinas Sosial Kabupaten - Kota - Audina Fitriana; Muhammad Arsyad (STMIK Banjarbaru, 2023)
The Hulu Sungai Selatan District Social Service as a distributor for distribution of compensation for victims of natural disasters has a problem with the current mechanism, namely the process of completing files must come directly to the village head's office, then to the sub-district office to make a recommendation letter. Then submit the file to the BPBD office directly. The distance between the Social Services Office and the BPBD office was quite far, which resulted in the file submission process being delayed. To overcome these problems, a web-based application is needed that can be accessed from anywhere. This research application development method applies the prototyping model. The design and design of this system uses UML (Unified Modeling Language), with a MySQL database and testing using User Acceptance. The existence of this application can simplify and speed up the process of registration or submission and distribution of assistance. Evidenced by the results of User Acceptance as much as 67% strongly agree and 33% agree that the application accelerates the process of distributing natural disaster compensation. Keywords: Applicatio; Compensatio; Natural Disaster AbstrakDinas Sosial Kabupaten Hulu Sungai Selatan sebagai distributor penyaluran santunan korban bencana alam memiliki kendala pada mekanisme yang berjalan saat ini yaitu proses kelengkapan berkas harus datang langsung ke kantor Kepala Desa, lalu ke Kantor Camat untuk membuat surat Rekomendasi. Kemudian menyerahkan berkas ke kantor BPBD secara langsung. Jarak antara Kantor Dinas Sosial dengan kantor BPBD yang cukup jauh mengakibatkan proses penyerahan berkas terlambat. Untuk mengatasi permasalahan tersebut dibutuhkan sebuah aplikasi berbasis web yang bisa diakses dari mana saja. Metode pengembangan aplikasi penelitian ini menerapkan prototyping model. Adapun perancangan dan desain sistem ini menggunakan UML (Unified Modelling Language), dengan basis data MySQL dan pengujian menggunakan User Acceptance. Adanya Aplikasi ini dapat mempermudah dan mempercepat dalam proses pendaftaran atau pengajuan dan pendistribusian bantuan. Dibuktikan dengan hasil User Acceptance sebanyak 67% sangat setuju dan 33% setuju bahwa aplikasi mempercepat proses penyaluran santunan bencana alam.